Santri Ethics from Kiai Kholil Yasin's Perspective (Study on Tiktok Content @kholilyasinofficial) - Agus Saifuddin Amin; Muhammad Sofi Ullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The development of various proselytizing media, one of which is tiktok social media as part of people's lives, has begun to be used by preachers to spread content with the theme of Islamic proselytizing, one of which is carried out by KH. Kholil Yasin with a tiktok account @kholilyasinofficial, the presence of tiktok social media as a medium of proselytizing can provide convenience for preachers in conveying messages in the form of Islamic proselytizing that can reach the wider community. Researchers are interested in researching the content of KH's proselytizing messages. Kholil Yasin on the tiktok account @kholilyasinofficial whose purpose is to find out how the content of Kiai kholil yasin's da'wah message in tiktok content. The research method used by researchers is in the form of a content analysis approach, which discusses in depth the content of information published or printed in mass media. The data collection technique used is in the form of documentation. Data analysis techniques used in the form of data reduction, data presentation and drawing conclusions. The content of the message that can be taken from the Tiktok Account @kholilyasinofficial if you want to become a successful student, namely eating well, getting enough sleep, reducing learning and feeling far away from the teacher, while if the student wants good knowledge and survives the afterlife, then the student must increase akhlakul karimah, khidmah and the last is a ban in the form of students prohibited from dating.